Estimation of NESFATIN-1 and VEGFA Levels in Iraqi Celiac Disease Patients Infected with Helicobacter pylori - Farah Hamza Mahdee; Shurooq Rayyis Kadhim; Wassan Abdulkareem Abbas (College of Pharmacy University of Baghdad, 2024)
Celiac disease is an autoimmune disease. It is associated with atrophy of the intestinal villi, leading to reduced absorbed nutrients. Nesfatin-1 is a peptide that is used as a laboratory detection tool in CD detection. VEGF plays a role in the permeability of endothelial functions. Helicobacter pylori are colonized and cause stomach injury in adults and children. H. pylori are cause chronic gastritis, duodenal ulcers, and adenocarcinomas. The study was estimated the NESFATIN-1 and VEGFA in CD with H. pylori. (41) CD with H. pylori and (31) CD without H. pylori, (42) control group is included in the study. Nesfatin-1 and VEGFA were measured in the entire participant. Nesfatin-1 was higher in CD than in the control group. It was lower in men than women and lowered in persons under 35 years of age than in persons over 35 years of age. VEGF was higher in patients with CD, it was higher in men than in women, and higher in persons less than 35 years of age than in persons with more than 35 years of age; also, it was higher in less than 35 years of age than in more than 35 years of age, a high level of VEGFA was detected in CD. VEGF expression change is reported in some tumors; it is unsuitable for detecting celiac disease but can be used for patients' follow-ups. CD cases have higher nesfatin-1 levels than in IBS-D or the control group. Deficiencies of minerals and vitamins are detected in CD patients irrespective of age and gender. All CD cases had nutritional deficiencies.